1948
DOI: 10.1302/0301-620x.30b1.59
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mould Arthroplasty of the Hip Joint

Abstract: I am particularly happy because this invitation implies recognition of the specialty of orthopaedic surgery. I am very grateful that you have chosen me as a representative of my specialty to give this lecture. Arthroplasty is an operative procedure undertaken for the purpose of creating a joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
5

Year Published

1974
1974
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(74 citation statements)
references
References 0 publications
1
68
0
5
Order By: Relevance
“…Although posterior approaches historically have been associated with higher dislocation rates [17,23,27], these appear to be improved with enhanced closure techniques [5,15,17,23]. The direct-anterior Hueter approach [32] is a modification of the traditional Smith-Petersen approach [18,44] in the interval between the rectus femoris and tensor fascia lata muscles and often uses a specialized table to allow for intraoperative anterior exposure and positioning of the hip [28,29]. Numerous authors have reported low dislocation rates and rapid early functional recovery [1,29,31,33,36,40,46] with this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Although posterior approaches historically have been associated with higher dislocation rates [17,23,27], these appear to be improved with enhanced closure techniques [5,15,17,23]. The direct-anterior Hueter approach [32] is a modification of the traditional Smith-Petersen approach [18,44] in the interval between the rectus femoris and tensor fascia lata muscles and often uses a specialized table to allow for intraoperative anterior exposure and positioning of the hip [28,29]. Numerous authors have reported low dislocation rates and rapid early functional recovery [1,29,31,33,36,40,46] with this approach.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of fibrous or hyaline cartilage in arthroplasties where skin (Kettunen 1958) or vitallium cups (Smith-Petersen 1948, 1952, Gibson & Williams 1951, Jakobsen 1957) have been applied as interposition materials has also been attributed to the factors of pressure and friction.…”
mentioning
confidence: 99%
“…Mould arthroplasty was first introduced in 1925 by Dr.Marius N Smith-Petersen [4,5] from Boston. He was used reactive synovial like membrane that he found in a piece of glass in the workman"s backyard.…”
Section: Review Of Literaturementioning
confidence: 99%